Response of the microbial community structure to the environmental factors during the extreme flood season in Poyang Lake, the largest freshwater lake in China - Zhang, Li; Yuan, Lijuan; Xiang, Jianjun; Liao, Qiegen; Zhang, Dawen; Liu, Jutao (Frontiers in Microbiology, 2024)
Background: Poyang Lake is the largest freshwater lake in China, and there have been several studies on the composition and diversity of bacteria in Poyang Lake, while few quantitative studies were carried out on the response of the bacterial community to the environmental factors during the extreme flood season in Poyang Lake.Methods: Connected-lake heterogeneity of bacterial community composition (BCC) was investigated in Poyang Lake during the flood season in 2020. Illumina high-throughput sequencing technology was applied in this study.Results: Bacterial community structure in water was different from that in sediment of Poyang Lake during extreme flood seasons. The bacterial diversity in water was much lower than that in sediment. In water column, the dominant phyla were Actinobacteriota, while the composition of bacteria in sediment was more complex than that in water, and the dominant phyla in sediment were Proteobacteria, Chloroflexi, Acidobacteriota and Actinobacteriota. The bacterial diversity in water of Poyang Lake showed seasonal dynamics, while no seasonal variation of bacterial communities in sediment was observed. The bacterial community structure in sediment from two bays and channel areas of Poyang Lake can be distinguished from each other. Microbial diversity in sediment gradually increased from Sancha bay to Zhouxi bay and then to channel, but the total nitrogen concentration (STN) and the total phosporus concentration (STP) in sediment showed opposite trends. This might be due to the anthropogenic disturbances from the extreme flood.The bacterial community structure in water column was not only sensitive to geochemical characteristics of water, but also affected by some nutrients concentration in sediment, especially STP. While the bacterial diversity during wet seasons was only sensitive to organic matter (SOM) and STP in sediment.Bacterial community structure in water was great different from that in sediment in Poyang Lake during extreme flood seasons. The bacterial community structure in water column was not only sensitive to geochemical characteristics of water, but also affected by some nutrients concentration in the sediment. While the bacterial diversity in sediment during wet seasons was only sensitive to SOM and STP.